Generic method for detecting focus time of documents. Issue 6 (November 2015) - Jatowt, Adam; Au Yeung, Ching Man; Tanaka, Katsumi
Highlights Statistical approach for estimating the focus time of text documents. Classification framework for categorizing documents into temporal and atemporal. Bi-Temporal Document Representation using document focus time and creation time.